Ambulatory blood pressure at sea level and high altitude in a climber with a kidney transplant and hypertension - Phelan, B; Mather, L; Regmi, N; Starling, J; Twillmann, D; McElwee, M; Paudel, P; Basnyat, B; Keyes, LE (Mary Ann Liebert, 2019)
Background and Objectives: High altitude may increase blood pressure (BP) and the kidney plays an important role in acclimatization. Little is known about how transplanted kidneys respond to the hypoxic stress at high altitude. We compared 24 hour ambulatory BP in a climber with a kidney transplant and hypertension at sea level and at high altitude (2860–4300 m).